Neutrophil-related indicators as potential peripheral blood biomarkers for the diagnosis of neurosyphilis: a cross-sectional study - Yijie Tang; Dandan Yang; Jiaqin Zhang; Lingyun Shen; Qinghui Xie; Qingqiong Luo (European Journal of Medical Research)
Abstract Background Neurosyphilis (NS) is the most serious complication elicited by the invasion of Treponema pallidum (T. pallidum) into the central nervous system. Identifying the neuro-invasion of T. pallidum as early as possible is important. Looking for indicators with good performance and convenient to operate is in great demand for the diagnosis of NS. Methods A cross-sectional study was conducted on 428 human immunodeficiency virus (HIV)-negative syphilis patients who underwent therapy in Shanghai Skin Disease Hospital from April 2022 to June 2023. The syphilis patients were further grouped into non-neurosyphilis (NNS), asymptomatic neurosyphilis (ANS) and symptomatic syphilis (SNS). Laboratory examination results of these patients were analyzed. Results Significantly elevated neutrophil CD64 (nCD64) index and neutrophil to lymphocyte ratio (NLR) were observed in ANS and SNS patients compared with those of NNS patients. nCD64 index and NLR were strongly correlated with serum and cerebrospinal fluid (CSF) TRUST titer, CSF WBC and CSF protein levels in NS patients. nCD64 index and NLR were independent factors influencing NS, especially ANS. Logistic regression models based on nCD64 index, NLR and serum TRUST titer exhibited better diagnostic performances to the currently used markers in NS diagnosis. Particularly, for NS patients with negative CSF TRUST, diagnostic performance of the combined nCD64 and NLR was obviously superior to CSF protein and CSF WBC. Conclusions Neutrophil-related indicators-nCD64 index and NLR have potential application value in the diagnosis of NS, especially for the CSF TRUST negative patients.